Chemical Characterization and Biological Activities of a Beverage of Zuccagnia punctata, an Endemic Plant of Argentina with Blueberry Juice and Lemon Honey - Correa Uriburu, Florencia Maria (2024)
In this study, the production of functional beverages of Zuccagnia punctata Cav. (jarilla), anative medicinal plant from Argentina, and Vaccinium corymbosum (blueberry), with lemon honey asa sweetener, is described. The beverage was formulated by using jarilla extract and blueberry juicewith maltodextrin as an encapsulant material. The beverage was dried by both spray-drying andfreeze-drying. Both beverages showed high water solubility with adequate features for handling,transport, and storage. The chromatic parameters indicate tones of mauve. Both the total polyphenol and flavonoid contents were retained after being spray-dried (92 and 100%, respectively). The anthocyanins were less stable under spray-dried conditions (58% retained). Both beverages showed high scavenger capacity on ABTS•+, HO•, and H2O2 (SC50 between 3.56 and 36.90 μg GAE/mL) and exhibited in vitro inhibitor potential of α-glucosidase, α-amylase, and lipase activities (IC50 of between 2.97 and 27.19 μg GAE/mL). The powdered beverage obtained by spray-drying presented the greatest preference in sensory tests. The beverages were neither toxic nor mutagenic in the concentration range with biological activity. During short-term storage, both beverages showed stability.The results obtained would support the use of a powdered beverage made from an Argentineannative plant and blueberries as a functional food.